ANTIPROTOZOAL ACTIVITIES OF COMPOUNDS ISOLATED FROM CROTON LOBATUS L - Lagnika, L.; Weniger, B.; Vonthron-Senecheaub, C.; Sanni, A (African Journal of Infectious Diseases (AJID), 2009)
In a preliminary evaluation of ethnobotanically selected Beninese medicinal plants for their in vitro antiplasmodial activity, the methanolic extract of the aerial parts of C. lobatus was found to have significant activity against P. falciparum, antileishmainal and antiprotoazoal assays carried out on some of the isolated compounds. Phytochemical investigation of this extract resulted in the isolation of five compounds: tiliroside (kaempferol-3-O-β-D-(6-E-p-coumaroyl) glycopyranoside) (1), isovitexin (apigenin-6-C-β-D-glucopyranoside) (2), vitexin (apigenin-8-C- β-D-glucopyranoside) (3), chlorogenic acid (acid-5-O-cafféoylquinic) (4) and 4,5-O-dicaffeoylquinic acid (5). Vitexin and tiliroside showed the best in vitro antiplasmodial activity against P. falciparum, with IC50 values of 4.4 and 7.1 µM, respectively. Vitexin also exhibited strong in vitro leishmanicidal and antitrypanosomal activities against Leishmania donovani amastigotes and Trypanosoma brucei rhodensiense trypomastigotes, with IC50 values of 0.6 and 0.1 µM, respectively.